2011
DOI: 10.1007/s10337-011-2009-3
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Benzoic Acid and Sorbic Acid in Food Products by CE after On-line Preconcentration by Dynamic pH Junction

Abstract: An online dynamic pH junction method has been proposed for sensitive determination of benzoic acid (BA) and sorbic acid (SA) by capillary electrophoresis (CE). It was based on the decreased mobility of the analytes when they migrated from sample zone with low pH to background electrolytes with high pH. Under optimized conditions, the limits of detection (S/N = 3) of BA and SA were 0.03 and 0.02 mg L -1 , respectively. According to the permitted limits of BA and SA in food (GB2760), the samples can be diluted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…However, excessive addition of some preservatives may induce health problems (allergy, dermatitis, convulsion, hives, etc.). The possibilities of CE to analyze food additives have been further demonstrated in the reviewed period including methods for the determination of benzoic acid and sorbic acid in beverages, vinegar, and fruit jam samples . A CE method was developed and compared with HPLC for the determination of benzoyl peroxide, as benzoic acid, in wheat flour, concluding that the performance of the CE method was comparable, and the quantitative results were in good agreement with those using HPLC.…”
Section: Food Additivesmentioning
confidence: 98%
“…However, excessive addition of some preservatives may induce health problems (allergy, dermatitis, convulsion, hives, etc.). The possibilities of CE to analyze food additives have been further demonstrated in the reviewed period including methods for the determination of benzoic acid and sorbic acid in beverages, vinegar, and fruit jam samples . A CE method was developed and compared with HPLC for the determination of benzoyl peroxide, as benzoic acid, in wheat flour, concluding that the performance of the CE method was comparable, and the quantitative results were in good agreement with those using HPLC.…”
Section: Food Additivesmentioning
confidence: 98%
“…Zhang et al used a dynamic pH junction method to improve the sensitivity of benzoic and sorbic acids, added as preservatives in food products . Detection limits of 30 and 20 μg/L were reported, respectively, which were 100 times lower than those without dynamic pH junction.…”
Section: Stackingmentioning
confidence: 99%
“…The principal mechanism takes advantage of velocity‐difference induced focusing, in which an analyte migrates differentially within two distinct segments of background electrolyte, resulting in the compression of the analyte into a narrow zone prior to its reaching the detector . Zhang et al demonstrated the scheme of dynamic pH junction and applied the technique for the preconcentration of benzoic acid and sorbic acid.…”
Section: Ce On‐line Stackingmentioning
confidence: 99%